Printability and fire performance of a developed 3D printable fibre reinforced cementitious composites under elevated temperatures - Weng, Yiwei (2020)
To demonstrate printability and fire performance of 3D printable fibre reinforced cementitious materials at elevated temperatures, large-scaling printing and fire performance testing are required for engineering applications. In this work, a mixture design of 3D printable fibre reinforced cementitious composite (3DPFRCC) for large-scale printing was developed. A structure with dimensions of 78 × 60 × 90 cm (L × W × H) was printed by a gantry printer in 150 min, which demonstrates that the developed 3DPFRCC mixture possesses good buildability. The rheological property, setting-time, and mechanical properties under normal and elevated temperatures of the developed 3DPFRCC were then characterised. Final results indicate that the developed 3DPFRCC is suitable for engineering applications due to its good printability and mechanical properties under normal and elevated temperatures.